Time-Dependent Modelling of Single-Electron Interferometry with Edge-States. (September 2015) - Beggi, A; Bertoni, A; Bordone, P
Abstract: We simulate the time-resolved dynamics of localized electrons in a 2DEG system, where an external magnetic field creates quantum Hall edge states, and properly polarized split gates define a Mach-Zehnder electron interferometer. The carriers travelling inside the Hall channels consist of localized wave packets of edge states: they are propagated numerically bymeans of a Fourier split-step approach. We find that the energy-dependent, scattering process at the quantum point contacts, together with the finite energy distribution of the carriers, have a remarkable effect on the transmission coefficient T of the device. We provide an analytical model to justify the characteristics of T which is in good agreement with the numerical simulations.